Nilai dan Loyalitas Pelanggan Restoran: Aplikasi Pemodelan Persamaan Struktural (SEM) - Muhammad Firdaus; Noor Annisya (School of Business, Bogor Agricultural University (SB-IPB), 2006)
Customer value and loyalty in many cases are often examined by using descriptive analysis. The usage of structural analysis for such cases in Indonesia is still limited. This study aimed to analyze the customer value and loyalty in a restaurant. Structural equation modelling is used to investigate the relationship between value and loyalty, and the factors which influence the customer value and loyalty. This study shows the positive relationship between such variables. Image is the most siginificant factor which influence the customer value.